Tracing the Roots of Error: A Polya Method Analysis on Student Problem Solving in Curved Surface Solids - Arifin, Zaenal; Bonyah, Ebenezer (EDUPEDIA Publisher, 2024)
When participating in this activity, students were tasked with recording and evaluating their responses to problems related to curved surfaces' geometry. The following difficulties were included in the scope of the investigation: spheres, cones, and cylinders. The researchers followed a four-step methodology developed by Polya to investigate the approaches and viewpoints of the students. This process included identifying the problem, developing a strategy, putting the strategy into action, and evaluating the results. According to the findings, it appears that the majority of errors occur when attempting to determine the nature of the issue. Using the appropriate formulas and procedures becomes quite difficult if the problem is misunderstood or not fully grasped. In the interest of assisting teachers in better assisting their students in developing stronger mathematical reasoning and understanding skills, this study will investigate real-life examples of students making improper mathematical applications. According to the research findings, it is suggested that mathematics education should incorporate more guided practice and conversation to assist students in developing their ability to solve problems. It is also highlighted throughout the study that it is necessary to have a complete comprehension of the problem statements.